Employee Performance at Grogol District Office, Sukoharjo Regency - Wijaya, Herdis Kurnia; Istiatin, Istiatin; Surdawarti, Surdawarti (Universitas Pamulang, 2025)
This research aims to determine the influence simultaneously (simultaneously) and partially of the variables of integrity, professionalism, compensation and career development on employee performance at the Grogol District Office, Sukoharjo Regency. This research method uses a quantitative research design. The population of all employees in Grogol District is 42 people. The sampling technique used in this research was a census sampling technique with a sample size of 42 people. Data collection using questionnaires. The data analysis techniques used for statistical analysis are multiple linear regression test, F test, t test, and coefficient of determination. The research results show that integrity, professionalism, compensation and career development partially and significantly influence employee performance at the Grogol District Office, Sukoharjo Regency. Suggestions from this research, the Grogol District Office, Sukoharjo Regency continues to improve existing integrity, professionalism, compensation and career development, so that employee performance will increase and be better than before.